Correlation of High Sensitive Troponin I (hsTnI) with Platelet Distribution Width (PDW) in Acute Myocardial Infarction Patients - Wulan, Aisyah Mayang; Rismawati Yaswir; Desywar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Acute myocardial infarction (AMI) occurs due to rupture of atherosclerotic plaque which triggers platelet activation and aggregation to form a thrombus. Several studies have examined the relationship between PDW and AMI, but there is no specific correlation with hsTnI as the most sensitive and specific cardiac biomarker for AMI. This study aims to analyze the correlation between hsTnI levels and PDW values in AMI patients. Methods: Cross-sectional study of 60 AMI patients in the emergency room of Dr. M. Djamil General Hospital Padang from April to August 2022. Research subjects who met the inclusion and exclusion criteria underwent hsTnI and PDW examinations. The correlation of hsTnI with PDW was analyzed using the Spearman correlation test. Correlation is declared significant if the p-value is <0.05. Results: The research sample consisted of 48 men (80%) and 12 women (20%). The average age is 60.67 (10.73) years with an age range of 33-82 years. The mean hsTnI level was 2,606.10 (2,404.79) ng/Land the mean PDW value was 10.97 (2.26) fL. There was a strong and significant positive correlation between hsTnI and PDW in AMI patients (r = 0.618, p = 0.000). Conclusion: There is a correlation between hsTnI levels and PDW values at AMI.